An oxime-based glycocluster microarray. Issue 24 (12th June 2017) - Hoang, Antoine; Laigre, Eugénie; Goyard, David; Defrancq, Eric; Vinet, Françoise; Dumy, Pascal; Renaudet, Olivier
Abstract : Carbohydrate microarrays represent powerful tools to study and detect carbohydrate-binding proteins, pathogens or cells. Abstract : Carbohydrate microarrays represent powerful tools to study and detect carbohydrate-binding proteins, pathogens or cells. In this paper, we report two original oxime-based methods to prepare surfaces displaying well-defined structures and valency in a given microspot with improved recognition potency with lectins. In a first "direct" approach, fully synthetic aminooxylated glycoclusters have been coated onto aldehyde-activated SiO2 (silicium substrate doped with 50 nm thermal oxide layer). To improve the preparation of the microarray in terms of rapidity and simplicity and to provide addressable surfaces on which sugars can be linked chemoselectively as clusters at defined plots, a second "indirect" strategy has been developed using successive oxime ligation steps. In both cases, binding assays with labelled lectins have revealed more potent and selective interaction due to the clustered presentation of sugars. The observed differences of interaction have been confirmed in solution by ITC.